The Plasmodium falciparum cell-traversal protein for ookinetes and sporozoites as a candidate for preerythrocytic and transmission-blocking vaccines. - Espinosa, D; Vega-Rodriguez, J; Flores-Garcia, Y; Noe, A; Muñoz, C; Coleman, R; Bruck, T; Haney, K; Stevens, A; Retallack, D; Allen, J; Vedvick, T; et al. (American Society of Microbiology, 2016)
Recent studies have shown that immune responses against the cell-traversal protein for Plasmodium ookinetes and sporozoites (CelTOS) can inhibit parasite infection. While these studies provide important evidence toward the development of vaccines targeting this protein, it remains unknown whether these responses could engage the Plasmodium falciparum CelTOS in vivo Using a newly developed rodent malaria chimeric parasite expressing the P. falciparum CelTOS (PfCelTOS), we evaluated the protective effect of in vivo immune responses elicited by vaccination and assessed the neutralizing capacity of monoclonal antibodies specific against PfCelTOS. Mice immunized with recombinant P. falciparum CelTOS in combination with the glucopyranosyl lipid adjuvant-stable emulsion (GLA-SE) or glucopyranosyl lipid adjuvant-liposome-QS21 (GLA-LSQ) adjuvant system significantly inhibited sporozoite hepatocyte infection. Notably, monoclonal antibodies against PfCelTOS strongly inhibited oocyst development of P. falciparum and Plasmodium berghei expressing PfCelTOS in Anopheles gambiae mosquitoes. Taken together, our results demonstrate that anti-CelTOS responses elicited by vaccination or passive immunization can inhibit sporozoite and ookinete infection and impair vector transmission.